The emergence of global regulatory coherence: A thorny embrace for China? - LIU, Han-wei (Institutional Knowledge at Singapore Management University, 2018)
The last two decades have witnessed various governance initiatives across institutions, domestic and international, in response to mushrooming regulatory trade barriers. Among the efforts to balance regulatory autonomy and international cooperation, “regulatory coherence” or “good regulatory practices” seems a promising solution that centers upon bottom-up domestic regulatory rationalization. While existing literature has documented how recent mega-regional trade blocs seek to harness regulatory barriers through mechanisms of international cooperation, it has arguably overlooked certain crucial issues. In particular, how has regulatory coherence emerged as a new global norm vis-à-vis the default international economic and legal order? What are the limits to the global normative diffusion of regulatory coherence when considering the diverse contexts and agendas of emerging economies, most notably China?